The Criticisms on the Orientalist’ Shubha and the Arguments on the Authenticity of the Qur’an - Mustaqim, Abdul (Universitas Islam Negeri Raden Mas Said Surakarta, 2020)
This article reconsiders the shubha (misgrounded conceit) proposed by the orientalists. The first shubha is about the revelation of the Qur’an; the second shubha is about the differences of qira’at (recitations or readings) claimed by the orientalists as proof that the Quran is not entirely authentic for the existence of false readings. The third shubha is about the authorship and the relationship of the Qur’an with previous divine books (Tawrat and Bible) showing that the Qur’an is a plagiarism work of The Prophet Muhammad or the notion of influence or borrowings from Judeo-Christian tradition. Employing the theological-historical approach, this article argues that, firstly, that the Qur’an is a Divine Revelation is evident from the linguistic style in which it very often uses direct speech to Muhammad, such as “Say, (O Muhammad to the mankind)”, and from the criticism posed by the Qur’an to Muhammad as the recipient of the revelation. Historically, the process of the writing of the Qur’an has started since the lifetime of the Prophet Muhammad and was based on reliable sources, either oral or written, supported by oaths from witnesses from the companions affirming the reliability of the existing records of the Qur’an during that period. Secondly, concerning the variation of the readings, if they are transmitted in mutawatir, they are the accepted readings, because theologically the Qur’an was revealed with differences of readings of sab’at aḥruf, in which there are a lot of ḥikma, and there is no contradiction. Finally, concerning the similarities (either the content or dictions) between the Qur’an and previous divine books, the notion of plagiarism is not relevant; it suggests the consistent and reliable chains of Divine Revelation between the messengers, making they are not in contradiction to the revelation received by the Prophet Muhammad (Q.S. Al-Nisa’[4]: 163-164). From the historical- philological perspective, the similarities of concepts or content between the Qur’an and Bible indicate that the Qur’an is in dialogue with the textual discourses found in its environment. It is reasonable because the Qur’an was not revealed in a vacuum context.